2003
DOI: 10.1152/jn.00533.2003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Morphological and Electrotonic Properties of Renshaw Cells, Ia Inhibitory Interneurons, and Motoneurons in the Cat

Abstract: . The morphological and electrotonic properties of 4 motoneurons, 8 Ia inhibitory interneurons, and 4 Renshaw cells were compared. The morphological analysis, based on 3-D reconstructions of the cells, revealed that dendrites of motoneurons are longer and more extensively branched. Renshaw cells have dendrites that are shorter and simpler in structure. Dendrites of Ia inhibitory interneurons could be as long as those of motoneurons but the branching structure resembled that of Renshaw cells. Compartmental mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 89 publications
(148 reference statements)
1
29
0
3
Order By: Relevance
“…Other work indicated that adult Renshaw cells receive polysynaptic excitation from ipsilateral group II and III muscle and cutaneous afferents (for review, see Baldissera et al, 1981). Monosynaptic connections from these afferents would be unlikely because they do not project (Brown, 1981;Fyffe, 1984) to ventral spinal cord regions containing Renshaw cell dendrites (Jankowska and Lindstrom, 1971;Lagerback and Kellerth, 1985;Alvarez et al, 1997;Bui et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Other work indicated that adult Renshaw cells receive polysynaptic excitation from ipsilateral group II and III muscle and cutaneous afferents (for review, see Baldissera et al, 1981). Monosynaptic connections from these afferents would be unlikely because they do not project (Brown, 1981;Fyffe, 1984) to ventral spinal cord regions containing Renshaw cell dendrites (Jankowska and Lindstrom, 1971;Lagerback and Kellerth, 1985;Alvarez et al, 1997;Bui et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Interneuron electrotonic properties were adopted according to data published by Bui et al (2003), but adjusted to a one-compartment interneuron model and with the added assumption that Ib interneurons are similar to Ia interneurons. For Renshaw cells, these values were adapted so that the membrane time constant could make the cell fire a burst of action potentials in response to a supra-threshold input (Hultborn and Pierrot-Deseilligny 1979).…”
Section: Motoneuron and Interneuron Modelsmentioning
confidence: 99%
“…Other typical examples include the relation between morphometric distributions that can be easily extracted from LM output and the electrotonic structure of the dendrites (e.g. comparing multiple classes of principal and inhibitory cells in the cat spinal cord 45 ). In some cases, the morphometric changes may be linked to the expression of growth factors activated during development.…”
Section: Potential Applications Of L-measurementioning
confidence: 99%